2020
DOI: 10.24018/ejfood.2020.2.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachta Indica A. Juss: Wood Ash Affects Seedling Growth of Mung Bean Vigna Radiata L.

Abstract: The burning of the wood ash is causing an environmental pollution related issue. The excess concentration of wood ash in the environment normally influenced on plant growth and development. This paper presents the effects of neem wood ash (Azadirachta inidca A. Juss.) on germination and seedling growth performance of mung bean (Vigna radiata L.) crop plants. Overall, the data reveals significant (p<0.05) effects of neem wood ash on the different growth variable of mung bean. The treatment of 4-20% neem wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Calcium carbonate soil conditioner performance on acidic soil has been researched and measured by the growth of crop plants, such as mung bean plant (Vigna radiata L.), which is one of the most important pulse crops grown all over the world that acts as one of the major sources of plant-based protein for humans [4]. The combination of calcium carbonate conditioning treatment combined with the usage of industrial NPK fertilizer has also been observed in several studies [12], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium carbonate soil conditioner performance on acidic soil has been researched and measured by the growth of crop plants, such as mung bean plant (Vigna radiata L.), which is one of the most important pulse crops grown all over the world that acts as one of the major sources of plant-based protein for humans [4]. The combination of calcium carbonate conditioning treatment combined with the usage of industrial NPK fertilizer has also been observed in several studies [12], [14], [15].…”
Section: Introductionmentioning
confidence: 99%